Global and national economic importance of pig meat production - Balogh, Péter (Acta Agraria Debreceniensis, 2017)
The pork production has changed significant in recent decades. Pig production fell significantly due to the need to adapt to new animal welfare rules in the sector. Furthermore, change in the meat consumption habit had also a negative effect on pig meat production. Hungarian pig sector and meat industry are in a difficult situation. Due to the high feed prices, the average production cost of pig farming has often exceeded the producer prices in recent years, therefore an increase of pig population could not be realised yet. Pig market is characterised by cyclical fluctuations of supply and prices, furthermore the decreasing producer price occurred parallel with increasing feed prices. Technology is also a critical fact in the Hungarian pig sector because there is a huge gap in the level of technology compared to that of competitive member states. With the development of production methods the efficiency of pork meat production can be improved in an environmentally friendly way.